Implementation of total quality management (TQM) and management by objectives (MBO) in university / Shaiful Azlan Abdul and Wan Kalthom Yahya - Abdul, Shaiful Azlan; Yahya, Wan Kalthom (2002)
Organization can practices any techniques or styles of management. It depends on the type of industry, the nature of business and the condition of the market and environment. MBO has been debated for more than 25 years either it work or not. TQM was popular in lately 80 's and early 90 'so Some company had proven successful after applied this concept and plan. UiTM is undergone of TQM and is still under process. The author trying to suggest how these concepts will be implemented without lessens each other. The suggestion and proposal will work in university environment.